The Psychology of Sustainability and Sustainable Development for Well-Being in Organizations - Di Fabio, Annamaria (Frontiers in Psychology, 2017)
This article discusses the contribution of the psychology of sustainability and sustainable development to well-being in organizations from a primary prevention perspective. It deals with sustainability not only in terms of the ecological, economic, and social environment but also in terms of improving the quality of life of every human being. The psychology of sustainability and sustainable development is seen as a primary prevention perspective that can foster well-being in organizations at all the different levels going from the worker, to the group, to the organization, and also to inter-organizational processes. The possibilities for further research and interventions are also discussed.